1985
DOI: 10.1029/ja090ia07p06608
|View full text |Cite
|
Sign up to set email alerts
|

The ultraviolet dayglow at solar maximum: 3. Photoelectron‐excited emissions of N2 and O

Abstract: Rocket observations of the far ultraviolet dayglow spectrum near solar cycle maximum are analyzed using laboratory cross sections, atmospheric composition models, and photoelectron production models. Photoelectron‐excited emissions of N2 and O are used to derive a self‐consistent description of the atmosphere at solar maximum. Spectral synthesis of the N2 Lyman‐Birge‐Hopfield bands shows a departure of a¹Πg state vibrational populations from the direct excitation theory. Observations of the N2 second positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Their model calculations reproduced the measurements if the O densities from the BNMS model were reduced by about 40~o, but their analysis was based on cross sections for electron impact production of emission at 1304 and 1356 ~_ reported by Stone and Zipf (1974) that were later reduced by a factor of 2.8 (Zipf and Erdman, 1985;Zipf, 1986). A model of the terrestrial dayglow oxygen emissions (Meier et al, 1985) suggested that the Stone and Zipf cross sections should be scaled down by 40~o. A reanalysis of the Pioneer Venus data using the renormalized cross sections showed good agreement between the O densities necessary to explain the measured emission and the BNMS model densities (Paxton and Meier, 1986).…”
Section: Species Sourcementioning
confidence: 78%
“…Their model calculations reproduced the measurements if the O densities from the BNMS model were reduced by about 40~o, but their analysis was based on cross sections for electron impact production of emission at 1304 and 1356 ~_ reported by Stone and Zipf (1974) that were later reduced by a factor of 2.8 (Zipf and Erdman, 1985;Zipf, 1986). A model of the terrestrial dayglow oxygen emissions (Meier et al, 1985) suggested that the Stone and Zipf cross sections should be scaled down by 40~o. A reanalysis of the Pioneer Venus data using the renormalized cross sections showed good agreement between the O densities necessary to explain the measured emission and the BNMS model densities (Paxton and Meier, 1986).…”
Section: Species Sourcementioning
confidence: 78%
“…Low-energy electrons play a strong role in auroral and dayglow activity [Cartwright, 1978;Doering et al, 1975]. A recent analysis of the N2 LBH system in dayglow and auroral observations by Meier et al [1985] suggest that threshold effects may play a role in understanding the processes, but it is apparent that other unexplained complications are present [Meier et al, 1985]. Figure 11…”
Section: Calibrationmentioning
confidence: 99%
“…The results obtained here should be particularly useful for model calculations of atmospheric phenomena in nitrogen systems. We have determined that the N2 LBH system, which apparently is an important component in the understanding of energy deposition and atmospheric physical chemistry [Meier et al, 1985], has a particularly simple excitation function. An accurate analytic fit to the cross section allows direct calculation of excitation effects over all energies above threshold.…”
Section: Calibrationmentioning
confidence: 99%
“…Extinction due to absorption by O 2 molecules in the Schumann-Runge continuum is important between 100 and 150 km altitude where O 2 is the predominant species (Meier, 1991). Contamination by the N 2 (a 1 g -X 1 + g ) LBH (3,0) band at 135.4 nm may also occur, especially in the bottom-side of the atmosphere, as explained in Meier et al (1985) and reaches 8 to 20 % of the overall emission at 200 km altitude depending on solar and atmospheric conditions. O + -O − neutralization may also play a role (around 5 % of the total emission), especially in the mid-latitude ionosphere (Meier, 1991;Dymond et al, 2000) and at low altitudes.…”
Section: Ionospheric Response: Modelling the Optical Emissionsmentioning
confidence: 99%